KARAKTERISTIK KOMPOSISI DAN STRATIFIKASI VEGETASI STRATA POHON KOMUNITAS RIPARIAN DI KAWASAN HUTAN WISATA RIMBO TUJUH DANAU KABUPATEN KAMPAR PROVINSI RIAU - Nursal '; Suwondo '; Irma Novita Sirait (Program Studi Pendidikan Biologi, 2013)
Research has been conducted to determine the composition and stratification characteristics Strata Trees Community Riparian Vegetation in the area of Lake Forest Tourism Rimbo Seven Kampar district in Riau Province in June 2012. The method used is the belt transect method with the size of 10 × 60 m plots were distributed on a regular basis. Riparian vegetation was found on all three stations for 14 species consisting of 10 tribes. The dominant vegetation composition at three stations located on tribal Euporbiaceae and Anacardiaceae. The results showed that for the three sites it was Stratification (standing vertically) in 3 study sites are in stratum B, with the highest vegetation Gluta renghas which has a height of 30 m. The results of measurements of environmental parameters in the forest region Rimbo seven lakes tour shows the highest temperature at the location of the new lake that is equal 31.660C.Keywords : Lake Forest Tourism Rimbo Seven, composition, stratification of riparian vegetation